2018
DOI: 10.21511/ppm.16(1).2018.02
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived organizational support and social comparison on work attitudes

Abstract: This study is based on the results of a survey research conducted by JobStreet Indonesia on its members, which has surprisingly found that more than 70% of employees lack clarity on the goals of their career. Drawing from the social exchange theory, employees tend to show positive work attitudes when they perceive that their organization paid attention to them. The objective of this study is to assess how significant the influence of Perceived Organizational Support (POS) is on career satisfaction, organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The rising turnover intention poses many challenges to the hotel sector in Jordan, which affects the plans and strategies of business management in this sector (Herachwati et al, 2018). The Jordanian market faces the continued rise in employee turnover intention creating many challenges, whether at the financial or administrative level, such as those related to re-employment, training, qualification, and development of new employees (Maqableh et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rising turnover intention poses many challenges to the hotel sector in Jordan, which affects the plans and strategies of business management in this sector (Herachwati et al, 2018). The Jordanian market faces the continued rise in employee turnover intention creating many challenges, whether at the financial or administrative level, such as those related to re-employment, training, qualification, and development of new employees (Maqableh et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Talent management is becoming a key instrument in adapting to these changes, as organizations need to decrease turnover intention and thereby avoid the costs of hiring new employees and those related to decreased organizational efficiency (Jenkins, 2009). Employee intentions to leave an organization and employee commitment to an organization are considered important factors that directly affect organization strategy (Cichy et al, 2009;Herachwati et al, 2018). Bhatnagar (2007) studied the effect of talent identification on employee attitudes, such as employee engagement, and how it could reshape employee attitudes towards leaving the company for another.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Many studies have confirmed that HRM practices contribute significantly to achieving job satisfaction, thus making employees closer and more engaged with their jobs (Sinniah & Kamil, 2017 The issue of employee turnover intentions and declining commitment of employees to their organizations is an important issue that affects organizations' strategies (Herachwati et al, 2018). This is due to the adverse effects on organizations caused by the increased TOI.…”
Section: Literature Reviewmentioning
confidence: 99%